THE IDEA OF CAPITALIST EXPLOITATION IN VICTORIAN ERA REPRESENTED IN CHARLES DICKENS’ OLIVER TWIST NOVEL - Ni, Ling Chen; Nasrullah, Nasrullah; Max, Jonathan Irene Sartika Dewi (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
In Victorian era, Capitalism was known as an economic system in which power was dominated by private ownership. The work system applied in Capitalism influenced the life of Victorian era and literary works recorded it. The aim of this research is to identify the idea of capitalist exploitation that exists and to describe how capitalist exploitation is represented through character, characterization, and setting in Oliver Twist novel. This research uses a theory by Mariano Zukerfeld about the types of capitalist exploitation which appear through alienation, reproduction, and attention. This is accomplished through library research and the use of a Historicism approach to identify capitalist exploitation in the Victorian era. The result of this research shows that capitalist exploitation is mostly experienced by Oliver Twist as a representative of the lower class. The researcher can conclude that the lower class character, which emerged from the working class, has been subjected to various forms of capitalist exploitation, such as exploitation through alienation refers to labor power, exploitation through reproduction refers to labor product, and exploitation through attention refers to labor time.